EDUCATIONAL PROJECTS WITH AN INTERNATIONAL DIMENSION FOR SENIORS AND THE HIGHER EDUCATION AND THE PROMOTION OF CULTURAL HERITAGE - María, Torres del Pilar García de la; Belver, Francisco Alscón (Estudos Interdisciplinares sobre o Envelhecimento, 2021)
Places that were and are scenario of our lives, are an intrinsic part of our identity, individual and collective. Both Cultural Heritage and Natural Heritage are constitutive elements of our way of life. The Senior University, the university program for older adults of the University of A Coruña, develops educational initiatives with an international dimension that promote knowledge of their own identity, but from a European and international perspective, through unique projects and initiatives that have the active participation of the students. This article will describe several experiences that, under the Erasmus + Program of the European Union, promote knowledge of Cultural Heritage among older adults in an international context.